PERBANDINGAN CAKUPAN ANTENATAL CARE TERHADAP KEJADIAN ANEMIA PADA PRIMIGRAVIDA DAN MULTIGRAVIDA - Fitria Ramadhani Puspitasari (FKU 16 UMY 032, 2016)
Background: One of program of the Millennium Development Goals (MDGs) which has not been achieved is to improve maternal health. This is influenced by the indicator Maternal Mortality Rate (MMR) is still high. Anemia in pregnancy is a high risk condition to mother and baby. Detection of early abnormalities in pregnant women could be reach by good perform of antenatal care covarage. Antenatal care coverage could be preventive effort to recognize dangerous signs in pregnant women. Objective: This study aimed to compare the effect of antenatal care coverage on the incidence of anemia among primigravida and multigravida. Methods: This study used comparative analytical observation with cross-sectional study design. The samples in this study were medical records of primigravida and multigravida who did antenatal care in Panembahan Senopati Hospital, Bantul in the period of January-December 2014. Sampling is conducted by simple random sampling method with 148 samples which is divided into two groups: primigravida and multigravida, with 74 samples for each. Data is analyzed using Chi-square test. Results: The result showed that there is no difference effect of antenatal care coverage to the number of anemia incidence in primigravida (p=0.104) and there is no difference effect of antenatal care coverage to the number of anemia incidence in multigravida (p=0.06). Conclusion: Based on research results, it can be concluded that there is no difference of antenatal care coverage's effect to the number of anemia incidence between primigravida and multigravida Keywords: antenatal care, anemia, primigravida, multigravida.